Helicobacter pylori, liver cirrhosis, and portal hypertension: an updated appraisal. (1st November 2016) - Licinio, Raffaele; Losurdo, Giuseppe; Carparelli, Sonia; Iannone, Andrea; Giorgio, Floriana; Barone, Michele; Principi, Mariabeatrice; Ierardi, Enzo; Di Leo, Alfredo
Abstract: Objective: Helicobacter pylori ( H. pylori ) is the most common cause of gastritis and peptic ulcer. However, H. pylori is even involved in extragastric diseases, and it has been hypothesized that H. pylori could be a risk factor for several hepatic diseases. For instance, a direct involvement of H. pylori in the development of portal hypertension (PH) in cirrhotic patients has been postulated. Methods: We performed a literature search in major databases to elucidate the relationship between H. pylori, portal hypertension, and liver cirrhosis. Results: The effect of H. pylori on PH may be multifactorial. Endothelial dysfunction, alterations in the vasodilating dynamics, and neoangiogenesis are the most appealing theories about this issue, but the proofs come mainly from experimental studies, therefore a solid pathophysiological basis is still to be demonstrated. Congestive gastropathy (CG) and gastric antral vascular ectasia (GAVE) are two common endoscopic entities responsible for acute/chronic upper gastrointestinal bleeding, and a link with H. pylori has been hypothesized: the gastric mucosa, exposed to H. pylori, could develop both inflammatory microcirculatory alterations and thrombi, resembling the histologic pattern of GAVE. Conclusions: Despite clues for an association between H. pylori and PH have been shown, these evidences are mostly experimental, therefore, in the absence of a direct proof on human beings, the role of H. pylori in the development of PH is uncertain. However, since this germ may be a cause of peptic ulcer, it should be found and eradicated in cirrhotic patients to reduce the risk of blood loss anemia.